(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Asthma is one of the most common chronic respiratory diseases in children, often presenting with acute exacerbations requiring prompt management in emergency settings. Salbutamol, a short-acting beta-agonist, is frequently used for rapid bronchodilation, delivered either via nebulization or metered-dose inhaler (MDI) with spacer. While nebulization is a traditional method, MDIs with spacers are emerging as an effective, convenient, and cost-efficient alternative. However, evidence comparing their clinical efficacy in pediatric emergency settings remains limited, particularly in resource-constrained environments. OBJECTIVE: To compare the clinical efficacy of salbutamol administered by metered-dose inhaler with a spacer by nebulizer for the treatment of asthmatic children in emergency. MATERIAL and METHODS: This Observational analytical comparative study was conducted at the Department of Paediatric Medicine Unit I, King Edward Medical University, Lahore / Mayo Hospital, Lahore, from November 2011 to March 2013.A total of 230 patients (age 5-12y) were included in the study after randomization. They were divided in two groups. In Group-1, 109 patients were included and nebulization technique was used. In Group-2, 111 patients were included and meter dose inhaler with spacer was used. Clinical efficacy was measured at 3hours of treatment. Modified pulmonary index score <9 and ≥20% increase in Peak exp flow rate were taken as parameters of improvement. Results: Group-1 patients had mean age of 8.2±2.59y compared to 7.57±2.23y in Group-2. in group-1was 27.5±6.7/min on admission and 21.9±5.6/min on discharge. In Group-2, mean resp rate was 27.5±5.6/min on admission and 21.8±5.0/min at discharge. in Group-1was 125.6±9.6/min on admission and 98.7±10.0/min at discharge. In Group-2, mean heart rate was 115.6±5.9/min on admission and 97.3±8.5/min at discharge. Mean Oxygen saturation in Group-1, was 90.9±0.84% on admission and 93.6±1.17% at discharge. In Group-2, mean oxygen saturation 90.15±7.81% on admission and 93.64±0.97% at discharge. Mean Peak expiratory flow rate (L/min) in Group-1 was 149.2±47.5 on admission and 199.2±64.9 at discharge. In Group-2, mean peak expiratory flow rate (L/min) was 152.4±46.9 on admission and 230.4±27.2 at discharge. Mean modified pulmonary index score in Group-1was 8.7±0.68 on admission and 6.2±0.87 at discharge. In Group-2, mean modified pulmonary index score was 8.6±1.15 on admission and 6.2±0.95 at discharge. In Group-1 56.9% were male and 43.1% were females. In Group-2 61.3% were male and 38.7% were female. Conclusion: Our results showed that clinical efficacy of both techniques measured as pulmonary index score < 9 and peak expiratory flow rate > 20% was achieved; hence both techniques were comparable and effective. Based on comparative efficacy, simplicity, convenience and financial advantages, meter dose inhalers with spacer can be recommended for use in children with asthma.